Tecnologias em energias renováveis: uma análise de alguns indicadores para países selecionados no período 1992-2018 - Storti, Dienifer Regina Fortes (2020)
The present study aimed to verify, through patent indicators on renewable energy, which scientific and technological efforts made by the twenty largest energy consuming countries in the world in the period 1992-2018. In addition, this study carried out a brief organizational and institutional analysis of this theme for China, the country that stood out the most in this theme. The results showed that the United States was ahead of most sectors throughout the period, although the most marked evolution was obtained by Asians countries, Japan, South Korea and China. European countries such as the United Kingdom and Germany lost space in terms of patenting in the area of renewable energies. The Chinese performance was the one that stood out the most. It was achieved both in terms of innovations and in terms of production and trade. The institutional analysis demonstrated the growing importance given by the Chinese government to renewable energies and China's intention to move towards an energy paradigm shift.